A decade of fundamentals of emergency care (FEC) course evaluation: Update from the last two years - Kamembela, Ilunga (Division of General Surgery, 2025)
Introduction: The Fundamental of Emergency Care (FEC) is a short course designed to give key skills and approaches to emergency care for non-specialist healthcare providers. This course has been running since 2012 primarily from the Western Cape of South Africa, open to all medical professionals for a fee. The course is conducted through self-study of a manual, and then two days of intensive skills and simulation based training. We undertook to survey and evaluate past participants of the course to assess the impact and suitability of the course, in order to improve and guide further iterations and expansion of the training. Method: We surveyed and analyzed all participants of FEC courses since inception using a series of email surveys. Descriptive statistics were performed using SPSS. The survey captured information about participants' profiles and opinions of the course. Results: Out of approximately 500 participants in 24 courses over the last decade, 210 (42%) took part in the surveys. The study revealed that a majority of the participants (67.6%) were medical doctors, with only a small percentage (14.76%) working full-time in emergency centres. The participants hailed from diverse backgrounds, including both rural and urban settings, and all facility levels. The overall consensus among respondents was that the course was well-presented, of affordable cost, and contained relevant content that they found useful in their respective practices. Conclusion: The FEC course has been established as a contextually relevant emergency short course for South Africa, providing an alternative to international courses which are often unaffordable, and may lack insights to local burden of disease and resource constraints. We believe that this is a model of training that can be expanded, locally adapted and remains feasible for local healthcare providers.